2020
DOI: 10.1021/acs.inorgchem.9b03093
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Coordination Chemistry of 3,4-Ethylene-Bridged 1,1,2,5-Tetrasubstituted Biguanides

Abstract: The synthesis of 3,4-ethylene-bridged 1,1,2,5-tetrasubstituted biguanides is reported, which are accessible by three alternative routes. Exemplary molecular structures of the ligand and an observed side product have been elucidated by X-ray diffraction analysis. Mono-and dinuclear complexes of the biguanide in both its neutral and monoanionic forms were obtained, including examples of aluminum, copper, magnesium, potassium, tin, and zinc, indicating a versatile coordination behavior, as evidenced by means of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Hence, each tetracoordinated potassium ion binds to the nitrogen atom N1 and the phenyl ring of the related Dipp group of one ligand in a κ 1 and η 6 mode, in κ 1 fashion to the N4 nitrogen atom of the next ligand and to one molecule of THF. The respective potassium-nitrogen bond lengths in the range of 2.695(2) to 2.735(2) Å, as well as the distance of the potassium ion to the centre of the C 6 perimeter (2.857(2) Å), are in good agreement with previously reported potassium complexes [22,26]. Hence, deprotonation occurs exclusively at N1, while the amino function at N5 remains intact, which is most likely due to the stabilization of H5 by the intramolecular N5H1•••N3 hydrogen bridge.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Hence, each tetracoordinated potassium ion binds to the nitrogen atom N1 and the phenyl ring of the related Dipp group of one ligand in a κ 1 and η 6 mode, in κ 1 fashion to the N4 nitrogen atom of the next ligand and to one molecule of THF. The respective potassium-nitrogen bond lengths in the range of 2.695(2) to 2.735(2) Å, as well as the distance of the potassium ion to the centre of the C 6 perimeter (2.857(2) Å), are in good agreement with previously reported potassium complexes [22,26]. Hence, deprotonation occurs exclusively at N1, while the amino function at N5 remains intact, which is most likely due to the stabilization of H5 by the intramolecular N5H1•••N3 hydrogen bridge.…”
Section: Resultssupporting
confidence: 90%
“…The crystalline yield of 1 amounts to 16%, although 1 is formed in 40% based on the crude 1 H NMR besides the carbothiamide 2 and the unsymmetric thiourea carrying one 2,6-diisopropylphenyl (Dipp) and one cyclohexyl substituent. Notably, such side products have also been observed in the synthesis of monoprotic biguanides [22]. Scheme 1.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…[27] At the time of drafting our manuscript, Kretschmer et al reported the 3,4-ethylene bridged 1,1,2,5-tetrasubstituted biguanides (Scheme 1, v). [28] As far as we know, tetra aryl-substituted conjugated bis-guanidines (CBG) are not known in the literature (Scheme 1). [29] Therefore, herein, we report a synthesis of structurally characterized CBGs by the reaction of amidoxime or aqueous (aq.)…”
Section: Introductionmentioning
confidence: 99%